2020
DOI: 10.18502/ijrm.v13i6.7282
|View full text |Cite
|
Sign up to set email alerts
|

Is gross morphology of placenta, umbilical cord, and neonatal outcome in well-controlled gestational diabetes mellitus pregnancy different? A case-control study

Abstract: Background: The relation of placental gross morphology and the outcome of pregnancies complicated with diabetes mellitus in comparison with healthy pregnancies is not known. Identifying significant differences in pregnancy outcomes in Gestational Diabetes Mellitus (GDM) and healthy pregnancies by the means of morphologic measurements can induce the use of antenatal ultrasonography of placental parameters to predict pregnancy outcomes. Objective: This study aimed to evaluate the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Kantorowska et al's retrospective cohort study of 176 mothers showed that improved remote patient monitoring of GDM mothers' blood glucose control could improve neonatal outcomes and reduce the incidence of neonatal sepsis [30]. A study that compared healthy pregnancies and well-controlled GDM in neonatal outcomes ( NICU admission rate) showed no differences [31]. However, our study suggests that GBS colonization in pregnant women with GDM during pregnancy increases the risk of neonatal sepsis, consistent with Mitanchez et al's ndings.…”
Section: Discussionmentioning
confidence: 99%
“…Kantorowska et al's retrospective cohort study of 176 mothers showed that improved remote patient monitoring of GDM mothers' blood glucose control could improve neonatal outcomes and reduce the incidence of neonatal sepsis [30]. A study that compared healthy pregnancies and well-controlled GDM in neonatal outcomes ( NICU admission rate) showed no differences [31]. However, our study suggests that GBS colonization in pregnant women with GDM during pregnancy increases the risk of neonatal sepsis, consistent with Mitanchez et al's ndings.…”
Section: Discussionmentioning
confidence: 99%
“…The umbilical cord of diabetes group sections stained with H & E of wharton’s jelly indicated that its fibers were disrupted and that large irregular empty areas resembling honeycombs were widely spaced. 8 , 13 , 14 , 19–29…”
Section: Histopathologic Impacts Of Gdm In Umbilical Cordmentioning
confidence: 99%
“…Furthermore, the smooth muscles of the umbilical arteries are disrupted, and their fibers degenerate. 14 , 15 As a result, GDM may have certain negative effects on the Wharton’s jelly’s umbilical arteries and connective tissue components.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it is widely described about GDM generating structural changes in the placenta such as increased placental weight (Table 1), leading to complicated pregnancies, influenced by decreased fetal oxygenation and increased lactate concentration (Pooransari et al, 2020;Bianchi et al, 2021). Legend: GDM -Gestational diabetes mellitus; GH -Gestational hypertension.…”
Section: Placenta and Gestational Diabetes: Morphological Characteris...mentioning
confidence: 99%